2017
DOI: 10.1096/fj.201601095r
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous anesthetic propofol binds to 5‐lipoxygenase and attenuates leukotriene B4production

Abstract: Propofol is an intravenous anesthetic that produces its anesthetic effect, largely the GABA receptor in the CNS, and also reduces the -formyl-methionyl-leucyl-phenylalanine (fMLP)-induced neutrophil respiratory burst. Because fMLP-stimulated neutrophils produce leukotriene (LT)B, we examined the effect of propofol on LTB production and Cecal ligation and puncture surgery was performed in mice, with or without exposure to propofol. Propofol attenuated the production of 5-lipoxygenase (5-LOX)-related arachidonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Azi‐isoflurane, azi‐sevoflurane, and m‐azipropofol (AziPm) are photoactivatable analogues of isoflurane, sevoflurane and propofol, respectively 22,24‐26 . Azi‐isoflurane (30 µM), azi‐sevoflurane (50 µM), or aziPm (10 µM) was equilibrated with TLR9 protein (1 mg/mL) in a reaction volume of 300 µL for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azi‐isoflurane, azi‐sevoflurane, and m‐azipropofol (AziPm) are photoactivatable analogues of isoflurane, sevoflurane and propofol, respectively 22,24‐26 . Azi‐isoflurane (30 µM), azi‐sevoflurane (50 µM), or aziPm (10 µM) was equilibrated with TLR9 protein (1 mg/mL) in a reaction volume of 300 µL for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Azi-isoflurane, azi-sevoflurane, and m-azipropofol (AziPm) are photoactivatable analogues of isoflurane, sevoflurane and propofol, respectively. 22,[24][25][26] Aziisoflurane (30 µM), azi-sevoflurane (50 µM), or aziPm (10 µM) was equilibrated with TLR9 protein (1 mg/mL) in a reaction volume of 300 µL for 10 minutes. Samples equilibrated with azi-isoflurane or azi-sevoflurane were exposed to 300 nm light using Rayonet RPR-3000 lamp (Southern New England Ultraviolet, Branford, CT, USA).…”
Section: Tlr9 Photolabeling Experiments Using Azi-anestheticsmentioning
confidence: 99%
“…Reverse‐phase mass spectrometry‐based quantitation technique was used for lipoxin A 4 (LXA 4 ) and maresin 1 (MaR1) measurement as previously described by Okuno et al . (27). The samples were diluted with 2 ml of methanol and 7 ml of water containing 0.1% formic acid containing a mixture of deuteriumlabeled eicosanoids as internal standards, and then loaded on Oasis HLB cartridge (Waters, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse-phase mass spectrometry (MS)-based quantitation technique for eicosanoids was previously described by Okuno et al (9). The lipids were extracted with methanol and diluted with water containing 0.1% formic acid to yield a final methanol concentration of 20%.…”
Section: Eicosanoid Lipidomicsmentioning
confidence: 99%
“…1C). Previously we have shown that intravenous anesthetic propofol directly bound to and attenuated 5-LOX (9). Thus, we tested if isoflurane also directly bound to 5-LOX using photoactivatable isoflurane (azi-isoflurane).…”
Section: Isoflurane Exposure Attenuated the Levels Of 5-lox Products ...mentioning
confidence: 99%